Flashcard-based physical education: Enhancing students’ physical fitness through visual-motor learning cues - Hambali, Sumbara; Hardi, Veny Juniarni; Yunisal, Papat; Akbaruddin, Asep (Jurnal Pendidikan Anak, 2025)
Physical education (PE) plays a pivotal role in fostering children's motor skills and physical fitness, especially at the primary school level. However, declining levels of physical activity and student engagement have prompted educators to seek more interactive and effective teaching strategies. This study aimed to examine the effectiveness of flashcard-based instruction in improving the physical fitness of elementary school students during PE lessons. Unlike previous studies that mainly applied flashcards for cognitive learning or basic motor instruction, this study examines their direct impact on physical fitness outcomes. This approach positions flashcards not only as conceptual aids but as visual-motor triggers designed to enhance exercise intensity and movement quality during PE lessons. A quasi-experimental design with a pre-test–post-test control group format was employed. A total of 84 fifth and six-grade students from two public elementary schools in West Java, Indonesia, participated in the study. The experimental group (n=42) received PE instruction integrated with flashcard media, while the control group (n=42) followed conventional PE lessons without media aids. Physical fitness was measured using the Indonesian Student Physical Fitness Test (TKSI) Phase C, comprising five test items. Data were analyzed using paired sample t-tests and independent sample t-tests. Both groups showed significant improvement in post-test scores (p < 0.05). However, the experimental group exhibited a significantly higher gain score (M = 5.12) compared to the control group (M = 2.34), indicating greater effectiveness of flashcard-based instruction. Flashcards enhance student engagement, comprehension, and movement execution in PE lessons. As a practical and low-cost instructional tool, flashcards hold promise for improving physical fitness outcomes among elementary school students, particularly in resource-limited educational settings.